# Maths Question ( Tricky)

Watch
Announcements

This discussion is closed.

Hey any of you good people know this answer it is for my homework:

2x=10-3y

3x+ 19=4y

Method and answer; i will be grateful

2x=10-3y

3x+ 19=4y

Method and answer; i will be grateful

0

Report

#2

(Original post by

Hey any of you good people know this answer it is for my homework:

2x=10-3y

3x+ 19=4y

Method and answer; i will be grateful

**Katchi_2003**)Hey any of you good people know this answer it is for my homework:

2x=10-3y

3x+ 19=4y

Method and answer; i will be grateful

2x=10-3y x3

3x=4y-19 x2

6x=20-9y

6x=8y-38

0=58-17y

y=58/17

0

Report

#3

**Katchi_2003**)

Hey any of you good people know this answer it is for my homework:

2x=10-3y

3x+ 19=4y

Method and answer; i will be grateful

6x = 8y - 38

17y - 68 = 0 , y = 4

2x = 10 - 3(4) = -2

x = -1

0

Report

#5

3y = 10-2x => y = (10-2x)/3

Substitute this into other equation:

4((10-2x)/3) = 3x + 19

(40-8x)/3 = 3x + 19

40-8x = 9x + 57

40-57 = 17x => x = -1

Then substitute into either of your original equations to get y.

Substitute this into other equation:

4((10-2x)/3) = 3x + 19

(40-8x)/3 = 3x + 19

40-8x = 9x + 57

40-57 = 17x => x = -1

Then substitute into either of your original equations to get y.

0

Report

#7

(Original post by

bhaal 10 x 3 = 30

**Lucy**)bhaal 10 x 3 = 30

0

(Original post by

Whoops.........that was meant to test you other peeps. lol.

**Bhaal85**)Whoops.........that was meant to test you other peeps. lol.

Man i done it but the check doesnt work, can someone show me how its done with full method and working, i be grateful.

0

Report

#9

Ok this is what I did:

First I rearranged the formulae:

2x = 10-3y (1)

3x = 4y-19 (2)

Then I did the formula (1) times 3 to make:

6x = 30 - 9y (3)

and I multiplied the formula (2) by 2 to make:

6x = 8y - 38 (4)

Then I did formula (4) minus formula (3) to make:

0 = 17y-68

therefore 17y=68

y = 4

I substituted y into formula (1) to get:

2x = -2

therefore x = -1

Substituted both values of x and y into (2) to check my values were correct.

Hope this is a bit clearer

First I rearranged the formulae:

2x = 10-3y (1)

3x = 4y-19 (2)

Then I did the formula (1) times 3 to make:

6x = 30 - 9y (3)

and I multiplied the formula (2) by 2 to make:

6x = 8y - 38 (4)

Then I did formula (4) minus formula (3) to make:

0 = 17y-68

therefore 17y=68

y = 4

I substituted y into formula (1) to get:

2x = -2

therefore x = -1

Substituted both values of x and y into (2) to check my values were correct.

Hope this is a bit clearer

0

(Original post by

Ok this is what I did:

First I rearranged the formulae:

2x = 10-3y (1)

3x = 4y-19 (2)

Then I did the formula (1) times 3 to make:

6x = 30 - 9y (3)

and I multiplied the formula (2) by 2 to make:

6x = 8y - 38 (4)

Then I did formula (4) minus formula (3) to make:

0 = 17y-68

therefore 17y=68

y = 4

I substituted y into formula (1) to get:

2x = -2

therefore x = -1

Substituted both values of x and y into (2) to check my values were correct.

Hope this is a bit clearer

**Lucy**)Ok this is what I did:

First I rearranged the formulae:

2x = 10-3y (1)

3x = 4y-19 (2)

Then I did the formula (1) times 3 to make:

6x = 30 - 9y (3)

and I multiplied the formula (2) by 2 to make:

6x = 8y - 38 (4)

Then I did formula (4) minus formula (3) to make:

0 = 17y-68

therefore 17y=68

y = 4

I substituted y into formula (1) to get:

2x = -2

therefore x = -1

Substituted both values of x and y into (2) to check my values were correct.

Hope this is a bit clearer

I Solved it in my way that method is right i [email protected]

2x+3y=10 > 1

3x-4y=19 > 2

>1 *4

8x+12y = 40 >3

>2* 3

9x-12y=57 > 4

8x+12y = 40 >3

9x-12y =57 > 4

4-3

1x=17

x=17

subst in 1:

34 + 3y = 10

3y = -24

y= -8

x=17

y= -8

check in 2:

51 - 32 = 19

3x-4y=19

thanks for all yr help

0

Report

#11

The formula you posted originally i.e. 3x +19 = 4y does not equal what you just posted now i.e. 3x - 4y = 19... it equals 3x - 4y = -19

0

Report

#12

(Original post by

solve simultaneously.

2x=10-3y x3

3x=4y-19 x2

6x=20-9y

6x=8y-38

0=58-17y

y=58/17

**Bhaal85**)solve simultaneously.

2x=10-3y x3

3x=4y-19 x2

6x=20-9y

6x=8y-38

0=58-17y

y=58/17

17y = 58

then u divide by 17 so u r left with

y= 58 divided by 17

0

Report

#13

(Original post by

AFTER THIS U ADD 17y to both sides so u have

17y = 58

then u divide by 17 so u r left with

y= 58 divided by 17

**CHAD**)AFTER THIS U ADD 17y to both sides so u have

17y = 58

then u divide by 17 so u r left with

y= 58 divided by 17

0

Report

#14

**CHAD**)

AFTER THIS U ADD 17y to both sides so u have

17y = 58

then u divide by 17 so u r left with

y= 58 divided by 17

0

Report

#15

(Original post by

We have already discovered that this is wrong as 2x=10-3y (x3) does not equal 6x = 20-9y therefore all the steps after that are incorrect (even though method is correct)

**Lucy**)We have already discovered that this is wrong as 2x=10-3y (x3) does not equal 6x = 20-9y therefore all the steps after that are incorrect (even though method is correct)

0

Report

#17

as u'r all talkin about maths..... is anyone doin the gcse maths c/wk where u have 2 find the difference of the products in a number grid??

0

Report

#18

(Original post by

as u'r all talkin about maths..... is anyone doin the gcse maths c/wk where u have 2 find the difference of the products in a number grid??

**Saf!**)as u'r all talkin about maths..... is anyone doin the gcse maths c/wk where u have 2 find the difference of the products in a number grid??

0

X

new posts

Back

to top

to top